Associated Ophthalmic Injuries in Patients With Fractures of the Midface. Issue 3 (September 2020) - Blumer, Michael; Rostetter, Claudio; Johner, Jean-Pierre; Ebner, Julian J.; Wiedemeier, Daniel; Rücker, Martin; Gander, Thomas
Purpose: Concomitant ophthalmic injuries are common in patients with facial fractures, though frequency varies widely in the literature. Major ophthalmic injuries can have drastic consequences for patients, and permanent visual impairment cannot be prevented in all cases. This study analyzed the frequency and distribution pattern of associated ophthalmic injuries in patients who received operative treatment for fractures of the midface. Material and Methods: The clinical information system was searched for patients with midface fractures that were treated operatively between December 2014 and November 2017. Demographic, fracture-related, and ophthalmic data were assessed and statistically analyzed. Results: This study included 282 patients. The most common fracture types were zygomaticomaxillary complex fractures and orbital floor fractures. Falls and violence were the most common causes of fractures (43.3% and 24.5%, respectively). Chemosis and subconjunctival bleeding were the most common associated eye injuries. The most prevalent long-term eye injury was diplopia, which was identified in 18.4% of cases preoperatively. Postoperative diplopia persisted in 36 cases (12.8%) at 3-month follow-up. Optic neuropathy, enophthalmos, exophthalmos, and retrobulbar hematomas were identified infrequently. Conclusion: Minor ophthalmic injuries, including chemosis and subconjunctival bleeding, are more frequently associated with midface trauma. These minor injuries tend to heal quickly and without sequela. Major ophthalmic injuries, including retinal detachment, optic neuropathy, and retrobulbar hematomas, are identified less frequently. Special attention should be paid to patients with diplopia, as this condition may persist and have long-term occupational consequences. Therefore, close interdisciplinary collaboration is essential when treating patients with fractures of the midface to prevent permanent visual impairment.